Legal Immunity of Advocates as a Constitutional Guarantee for Access to Justice and Democratic Accountability: Legal Immunity of Advocates as a Constitutional Guarantee for Access to Justice and Democratic Accountability - Iwan Chandra; Atma Suganda; Tubagus Achmad Doradjat (PENA LAW: International Journal of Law, 2026)
Advocates are essential to upholding the rule of law and ensuring access to justice; yet, they often face intimidation and criminalization when handling sensitive cases. While international instruments, such as the United Nations Basic Principles on the Role of Lawyers (1990), recognize the importance of legal immunity, its constitutional protection and implementation vary significantly across jurisdictions. Employing a normative juridical approach that integrates doctrinal, comparative, and conceptual analyses, this study finds that European legal systems generally provide stronger constitutional safeguards. In contrast, many Latin American and Asian jurisdictions offer comparatively weaker protections. The findings affirm that advocates’ immunity is not merely a professional privilege but a constitutional guarantee essential to equal access to justice and democratic accountability. This study contributes to scholarly discourse by reframing advocates’ immunity within a constitutional and democratic framework. It further offers practical recommendations for policymakers and professional associations to strengthen legal protections, thereby enhancing both the independence of advocates and the resilience of democratic systems.